If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + -2 = 143 Multiply x * x x2 + -2 = 143 Reorder the terms: -2 + x2 = 143 Solving -2 + x2 = 143 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x2 = 143 + 2 Combine like terms: -2 + 2 = 0 0 + x2 = 143 + 2 x2 = 143 + 2 Combine like terms: 143 + 2 = 145 x2 = 145 Simplifying x2 = 145 Take the square root of each side: x = {-12.041594579, 12.041594579}
| (6x+5)(8x^2+7x+4)=0 | | -6=2x-x+4 | | -2(7+11)=6 | | -2(a+3)-9=0 | | y-7=180 | | -5b=-65 | | 2(1)+6(0)=2 | | 18x=3+3y | | x-9=-4+8 | | 2.35+p+14.9=1 | | (6x+5)(8x^2+7x+4)= | | 5x-5=9x-5 | | 4x+2+5x=110 | | 6n^2-18n-18-6=0 | | -3(2s-3)-9=-3(5s+1)-5 | | (X-16.5)(x-109)=0 | | -3-5(-3x+3)=105 | | 3(4x*-1)=12x | | 4m=2(7m+30) | | 2(2+r)-3r=r+8 | | y=-4(1)+9 | | p^2-9-6=0 | | 24x+24=-36x-8 | | -4x-1=27 | | X+5=6x-45 | | 2t^2-5t+2=0 | | -3x+7=2x+42 | | -26=4+6x | | y=-3(-2)-6 | | 5.66s-5=25.78 | | 6x+2=6x-45 | | 0.1x^2=0.169 |